2022
DOI: 10.1039/d2nr00728b
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon relaxation at the Au/WSe2 interface is significantly accelerated by a Ti adhesion layer: time-domain ab initio analysis

Abstract: On introduction of a thin Ti adhesion layer at the Au/WSe2 interface, the electron–phonon coupling strengthens which results in accelerated excited charge carrier relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The p-terminal current (20 nA) is slightly higher than the n-terminal current (17 nA) in Figure S2a. A previous study demonstrated that the ambipolar behavior can be explained based on Fermi-level shifting under the electric field because of the weak Fermi-level pinning at the metal/WSe 2 interface. The balanced electron and hole transport characteristic results from identical n- and p-type Schottky barriers …”
Section: Resultsmentioning
confidence: 99%
“…The p-terminal current (20 nA) is slightly higher than the n-terminal current (17 nA) in Figure S2a. A previous study demonstrated that the ambipolar behavior can be explained based on Fermi-level shifting under the electric field because of the weak Fermi-level pinning at the metal/WSe 2 interface. The balanced electron and hole transport characteristic results from identical n- and p-type Schottky barriers …”
Section: Resultsmentioning
confidence: 99%
“…The NA-MD simulations were performed using the decoherence-induced surface hopping (DISH) technique implemented in TD-DFT based on the Kohn–Sham (KS) framework. , Decoherence is the destruction of the superposition state formed by a pair of electronic states in the system via NAC. , The decoherence time can be estimated as the pure-dephasing time in optical response theory . In the DISH algorithm, quantum jumps occur as a result of the decoherence process, which provides the physical basis for the jumps. ,, This method has been applied to study the photoexcitation dynamics of various materials, including metal oxides, low-dimensional materials, perovskites, ,,,, and other systems. , …”
Section: Methodsmentioning
confidence: 99%
“…We also investigate the dynamics of hot carriers by tracking electron and hole differences separately. Most theoretical studies use an energy-space analysis for plasmonic hot carriers, for example, hot carrier distributions and scattering lifetimes as functions of their energy, or evolving these hot carrier energies and densities over time. ,,, In this work, we use a simplified version of this analysis, where changes in occupation above (below) the Fermi level are assigned as electrons (holes), resulting in gross atomic assignment of negative (positive) charges on each atom. We get the transition probability of electron from an occupied Kohn–Sham state o to an unoccupied Kohn–Sham state u , creating a hole, from the change in density matrix, P o u ( t ) = | δ ρ o u false( t false) f o f u | 2 where f o ( u ) is the occupation number associated with the electronic states of o ( u ) below (above) the Fermi energy level.…”
Section: Methodsmentioning
confidence: 99%